Development of Teaching Materials in the Form of Daras Books Student Management Courses - Herma Yulis Syam; Vicky Rizki Febrian; Wilma Rahmah Hidayati (Ta'dib, 2023)
This study aims to develop teaching materials in the Student Management Study Program to determine the feasibility of teaching materials in improving the quality of classroom learning.  This research was development research adapted from the ADDIE model. There are five stages of this research, namely: 1. Analysis 2. Design, 3. Development, 4. Implementation, and 5. Evaluation. Validation was carried out by material experts, media experts, linguists, and practicality assessments from MPI students at UIN Mahmud Yunus Batusangkar. Based on the assessment of validators, the first material expert scored aspects of the material presentation 3.4 (85%), and the second material expert scored 3.6 (90%) of the maximum score of 4.0. The results from the first material expert validator in the aspects of content eligibility were 3.4 (85%), and from the second material expert aspects of content feasibility were 3.2 (80%) of the maximum value of 4.0. The validation results from the first media expert validator were 3.4 (85% and the second media expert was 3.4 (85%) from a maximum value of 4.0, namely in the aspect of language feasibility; all aspects of the validator regarding the textbook of student management have been suitable to use as learning media for student management courses in improving the quality of learning.